The effectiveness of palm oil fuel ash (POFA) to resist chloride ion in concrete - Mohd Zhafir, Mohd Jais (2013)
In nowadays construction, the demand for high performance and high durability of concrete is highly required to be used in reinforced concrete structure. The use of new material to product concrete with good quality has encouraged this study to be conducted. Corrosion of reinforcement is one of the most crucial problems for most of reinforced concrete structure because the corrosion can reduce the strength of the structure. A new by-product from palm oil mill that is POFA is used in this scope of study. POFA was found as pozzolanic material which is can replace cement in concrete production. The pozzolanic reaction that occurs can help to strengthen the concrete and enhance the concrete durability. In this study, cement has been replaced with 10%, 20% and 30% of POFA as cement replacement material. Specimens have been tested to measure the effect of POFA toward compressive strength test, impressive voltage test, half-cell test and acid soluble test. From the result of the laboratory testing, it is prove that concrete with 20% of replacement of POFA is the best composition from all the four compositions. In matter of strength, corrosion resistance and chloride diffusion, the results show that composition of 20% of POFA was produced the best result while compare to the control sample give the lowest result. As conclusion, POFA can be used as cement replacement which can produce good durability to the concrete with better corrosion resistance due to lower the penetration of ion chloride and slow the rate of corrosion inside the concrete.